2012
DOI: 10.1073/pnas.1214240110
|View full text |Cite
|
Sign up to set email alerts
|

Human trichromacy revisited

Abstract: The presence of a photopigment (melanopsin) within certain retinal ganglion cells was a surprising and significant discovery. This pigment is routinely described as "nonvisual" to highlight its signaling role in pupil dilation and circadian rhythms. Here we asked whether light absorbed by melanopsin can be seen by healthy human subjects. To answer this requires delivering intense (above rod saturation), well-controlled lights using four independent primaries. We collected detection thresholds to many four-prim… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
69
0

Year Published

2013
2013
2022
2022

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 66 publications
(71 citation statements)
references
References 48 publications
(71 reference statements)
2
69
0
Order By: Relevance
“…In contrast, the five-primary approach we used will yield a unique solution for a certain combination of the excitations of the five types of photoreceptors. Thirdly, another group also reported developing a six-primary photostimulator to study the contribution of melanopsin to chromatic discrimination (Horiguchi et al, 2013;Horiguchi, Winawer, Wandell, & Dougherty, 2011). However, they decided not to use all of the six primaries because of the difficulty in accounting for individual variability in the transmission of the cornea and lens.…”
Section: Discussionmentioning
confidence: 97%
See 1 more Smart Citation
“…In contrast, the five-primary approach we used will yield a unique solution for a certain combination of the excitations of the five types of photoreceptors. Thirdly, another group also reported developing a six-primary photostimulator to study the contribution of melanopsin to chromatic discrimination (Horiguchi et al, 2013;Horiguchi, Winawer, Wandell, & Dougherty, 2011). However, they decided not to use all of the six primaries because of the difficulty in accounting for individual variability in the transmission of the cornea and lens.…”
Section: Discussionmentioning
confidence: 97%
“…IpRGCs project to brain areas associated with non-imageforming functions, such as the SCN for circadian photoentrainment Ruby et al, 2002) and the olivary pretectal nucleus (OPN) for controlling pupil size (Clarke, Zhang, & Gamlin, 2003;Hattar et al, 2002;Lucas et al, 2003). IpRGCs also project to the LGN (Berson, 2003;Dacey et al, 2005) and may contribute to image-forming processes Brown et al, 2012;Horiguchi, Winawer, Dougherty, & Wandell, 2013;Zaidi et al, 2007).…”
Section: Introductionmentioning
confidence: 98%
“…For nonimage vision, although adaptation is certainly beneficial for increasing the signaling dynamic range, the exact implication of Weber-Fechner behavior is less obvious. Because ipRGCs are now known to also contribute to conscious vision (12,(48)(49)(50)(51)(52), this adaptation behavior may have more to do with the latter function. It would, thus, be useful to know whether the other ipRGC subtypes [which supposedly are more involved in image vision compared with M1 cells (12,15)] show similar adaptation behavior.…”
Section: Discussionmentioning
confidence: 99%
“…It has been reported that humans lacking an outer retina [39] or animals with rods and cones ablated genetically [40] can preserve some light detection functions. In people with normal retinas, melanopsin activation could contribute to brightness discrimination [40], chromatic discrimination [41], color perception [42,43] and contrast sensitivity [4,44]. However, the mechanisms for melanopsin activation affecting conscious visual perception are not well-understood.…”
Section: Impact On Visual Perceptionmentioning
confidence: 99%